Understanding Psychosis: Issues, Treatments, and Challenges for Sufferers and Their Families - Capps, Donald (Rowman & Littlefield Publishers, 2010)
When a loved one is struck with psychosis, people often misunderstand what is happening and why. They may feel helpless or confused or frightened, not knowing what to do with or for the sufferer or how to handle the situation themselves. This book takes a look at psychosis and how it has been handled over the last century or so. Beginning with a definition of psychosis and moving to a consideration of how people who suffer from it were once institutionalized and are now expected to be cared for at home, the author traces the challenges families and communities face, considers the plight of sufferers and what they experience, and offers case examples throughout to illustrate the onset of psychosis, the infringement it makes on personal and professional life, and the toll it takes on sufferers and caregivers alike. Capps covers the magnitude of the problem, the treatment of sufferers, the warning signs, facts and realities of recovery, treatments, prevention, and coping strategies for family members and caregivers. Readers will come away from this work with a better understanding of psychosis in the context in which it occurs, and what to do for themselves and their loved one as they navigate daily life, the mental health system, and family dynamics.